2018
DOI: 10.1111/codi.13982
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy conversion after flexible sigmoidoscopy screening: results from the UK Bowel Scope Screening Programme

Abstract: Male gender, polyps ≥ 10 mm and villous-preponderant histology at FS were predictors of adenomas < 10 mm and ≥ 10 mm at colonoscopy. Further data are required to assess the role for gender-based stratification of conversion criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Within the UK Bowel Scope guidelines, the presence of adenomas ≥10 mm is an indication for colonoscopy to exclude proximal lesions 44 45. It is reasonable to expect endoscopists in FS to resect lesions <10 mm.…”
Section: Recommendation Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the UK Bowel Scope guidelines, the presence of adenomas ≥10 mm is an indication for colonoscopy to exclude proximal lesions 44 45. It is reasonable to expect endoscopists in FS to resect lesions <10 mm.…”
Section: Recommendation Statementsmentioning
confidence: 99%
“…Within the UK Bowel Scope guidelines, the presence of adenomas ≥10 mm is an indication for colonoscopy to exclude proximal lesions. 44 45 It is reasonable to expect endoscopists in FS to resect lesions <10 mm. As SMSA has replaced size criteria alone for evaluating difficulty of polypectomy (ie, level 1: <10 mm polyp; level 2: 10–20 mm polyp), competency in FS should include competency in SMSA level 1 polyps as a minimum.…”
Section: Recommendation Statementsmentioning
confidence: 99%
“…For instance, in MiMiC-Bowel the adjustment of definitions of pre-cancer states were based on the UK Flexible Sigmoidoscopy Screening randomized controlled trial (UKFSST), which was the only data source that reported detection of advanced and HRA [16]. However, the detection rates of CRC and HRA were higher in the trial compared with the subsequent Bowel Cancer Screening Programme (BCSP) in England and this discrepancy has been ascribed to the inclusion criteria and uptake characteristics [34,35].…”
Section: Reasons For Indirect Uncertainty In Calibration Targetsmentioning
confidence: 99%
“…Flexible sigmoidoscopy (FS) is the third most commonly performed lower gastrointestinal examination in the UK, with ove r 5 0 0 , 0 0 0 pro c e du re s performed each year [1]. Flexible sigmoidoscopy is the first line investigation for anorectal symptoms and it is a primary colorectal cancer screening modality in England and Canada [2]. Over the last two decades, the focus on colonoscopy quality has catalysed reforms in colonoscopy training, instigating competency-based curricula, research into skills acquisition, and the development of a plethora of direct observational competency assessment tools to assure quality training [3].…”
Section: Introductionmentioning
confidence: 99%